Effective Discipline with Adequate Autonomy : The Direction for Further Reform of China's SOE Dividend Policy - Zhang, Chunlin; Wang, Lihong (World Bank, Washington, DC, 2014)
This note explores the desirable direction for further reform of China's state-owned enterprise (SOE) dividend policy. This study represents an effort in exploring the desirable direction for further reform. It is an extension of the previous World Bank studies (World Bank, 2005, 2007) on this subject. It argues that a sound dividend policy must generate effective discipline against insiders and leave adequate managerial autonomy to them in the meantime. Considering China's current situation in light of relevant international experience, this study recommends three actions for the government to take to deepen the reform. The first is to raise the flexibility of SOE dividend ratio by adding a dividend ratio determination mechanism to the existing system of state ownership function. The second involves government monitoring and adjustment of the average dividend ratio of all central SOEs. The third is to start integrating state capital management budget (SCMB) with the general budget. The rest of the note is organized as follows. Section two discusses the nature of the issue and the criteria that a sound dividend policy must meet. Section three-five reviews payout practices of private sector firms (mainly publicly held companies but also include privately held firms), non-Chinese SOEs, and Hong Kong listed Chinese SOEs. Section six presents recommendations regarding the direction for further reform.